Ethnicity and Health Literacy: A Systematic Review of Cultural and Linguistic Challenges in Healthcare - Handayani, Annisa Awalia (Journal of Health Literacy and Qualitative Research, 2023)
Health literacy is a key driver of health equity, yet persistent gaps remain among ethnic minorities. Following PRISMA 2020 guidelines, we searched PubMed, Scopus, and Google Scholar for English language studies published between January 2013 and December 2023 using the terms “health literacy,” “ethnicity,” “cultural competence,” and related keywords. Inclusion criteria comprised empirical investigations reporting quantitative or qualitative data on health literacy outcomes stratified by ethnicity. Two reviewers independently screened 6,124 records, appraising methodological quality with the JBI critical appraisal tools; 97 articles met all criteria. Low socioeconomic status, limited language proficiency, and culturally incongruent services consistently predicted inadequate health literacy across settings. Evidence based digital interventions such as bilingual telehealth portals (e.g., MiSalud), culturally tailored SMS programmes like Text4baby that increased prenatal visit adherence by 18 percent among Latina users (5), and community embedded mobile apps for chronic disease self management demonstrated measurable improvements in comprehension and self care. Ethnic disparities in health literacy can be reduced through intersecting policy, clinical, and technological innovations that recognise culture and language as central determinants of health.